2015
DOI: 10.1038/srep08579
|View full text |Cite
|
Sign up to set email alerts
|

Cardioprotective activity of iron oxide nanoparticles

Abstract: Iron oxide nanoparticles (IONPs) are chemically inert materials and have been mainly used for imaging applications and drug deliveries. However, the possibility whether they can be used as therapeutic drugs themselves has not yet been explored. We reported here that Fe2O3 nanoparticles (NPs) can protect hearts from ischemic damage at the animal, tissue and cell level. The cardioprotective activity of Fe2O3 NPs requires the integrity of nanoparticles and is not dependent upon their surface charges and molecules… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
71
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 78 publications
(75 citation statements)
references
References 34 publications
4
71
0
Order By: Relevance
“…Iron oxide nanoparticles have also been investigated as cardioprotective agents, as shown by Xiong et al (2015). The authors demonstrated the potential of maghemite NPs for protecting the heart from ischemic damage both in vivo and in vitro.…”
Section: Inorganic Nanoparticlesmentioning
confidence: 97%
“…Iron oxide nanoparticles have also been investigated as cardioprotective agents, as shown by Xiong et al (2015). The authors demonstrated the potential of maghemite NPs for protecting the heart from ischemic damage both in vivo and in vitro.…”
Section: Inorganic Nanoparticlesmentioning
confidence: 97%
“…Brain injury repair mechanism of PtPdMo nanozyme with high catalytic activity and neutral environment preference [29] (color online) 图 3 Fe 2 O 3 @DMSA-NPs对大鼠冠状动脉结扎(CAL)损伤的保护作用 [32] (网络版彩图) Figure 3 Fe 2 O 3 @DMSA NPs protected coronary artery ligature (CAL) induced injury in rats [32] (color online) [39] (网络版彩图) Figure 4 Schematic and curative effect for N-PCNSs induced tumor cell destruction via ferritin-mediated specific delivery [39] (color online)…”
Section: 目前 癌症是全球人口的主要死因之一 21世纪预mentioning
confidence: 99%
“…14,15 While, beneficial effects of IRONs on electrical transduction and cardiac function were recently revealed by researchers. 16,17 IRONs as MRI contrast agent improved the infarcted myocardium function due to the improvement of possible myocardium remodeling in vivo. 18 Moreover, connexin 43 expression and the assembly of gap junctions of cardiomyocytes in two-dimensional (2D) environment was augmented by IRONs.…”
Section: Introductionmentioning
confidence: 99%
“…In terms of the effects of IRONs on cardiac tissues and stem cells, a few of studies indicated that IRONs performed rare effects on cardiomyocytes including cardiac mitochondrial respiratory chain complexes activities and the differentiation of embryonic stem cells toward cardiomyocytes . While, beneficial effects of IRONs on electrical transduction and cardiac function were recently revealed by researchers . IRONs as MRI contrast agent improved the infarcted myocardium function due to the improvement of possible myocardium remodeling in vivo .…”
Section: Introductionmentioning
confidence: 99%